2018
DOI: 10.1080/14685248.2017.1418085
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical investigation of free-stream turbulence effects on the transition-in-wake state of flow past a circular cylinder

Abstract: This work investigates how a turbulent free-stream (TFS) affects the transition-inwake state of flow past a cylinder. Direct numerical simulations have been performed, where the intensity of a decaying TFS varied from 3.6% to 12.2% (as it reaches the cylinder), with integral scales 0.5, 0.75 and 1.0 times the cylinder diameter for the high intensity case. Distinct effects of the TFS are observed for Reynolds numbers in the lower (Re < 190) and upper (Re ≥ 250) ranges of the transitional regime. For a flow with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This conclusion was also drawn, for instance, with studies that focused on end-effects (Williamson, 1989;K€ onig et al, 1992). More recently, numerical studies have also captured the presence of phase dislocations, both for uniform cylinders (Braza et al, 2001;Aarnes et al, 2018) and for tapered cylinders (Kaja et al, 2016). Moving closer to the present application, Yang et al (2013) reported simulations of a flat plate at low inclination angles, linking the appearance of phase dislocations with the distinct characteristic frequencies of the normal shedding and the parallel shedding.…”
Section: F Relation Between the Transferred Power And The Wakementioning
confidence: 64%
“…This conclusion was also drawn, for instance, with studies that focused on end-effects (Williamson, 1989;K€ onig et al, 1992). More recently, numerical studies have also captured the presence of phase dislocations, both for uniform cylinders (Braza et al, 2001;Aarnes et al, 2018) and for tapered cylinders (Kaja et al, 2016). Moving closer to the present application, Yang et al (2013) reported simulations of a flat plate at low inclination angles, linking the appearance of phase dislocations with the distinct characteristic frequencies of the normal shedding and the parallel shedding.…”
Section: F Relation Between the Transferred Power And The Wakementioning
confidence: 64%
“…In this study, we will stick to the more mature method of using mirror-points from surface normals. Details on the alternative grid-line ghost-zone IBM can be found in Aarnes et al (2018b).…”
Section: Ghost-zone Immersed Boundary Methodsmentioning
confidence: 99%